2020
DOI: 10.2174/1570162x18666200106150806
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Supplement Attenuate Bone Loss among HIVInfected Patients Receiving Tenofovir Disoproxil Fumarate/Emtricitabine/ Efavirenz: An Open-Label, Randomized Controlled Trial

Abstract: Background: Antiretroviral therapy (ART), especially with tenofovir disoproxil fumarate (TDF), has been associated with accelerated bone turnover and leads to significant bone loss. Objective: We aimed to determine the effect of vitamin D2 and calcium on bone mineral density (BMD) in HIV-infected patients receiving TDF/emtricitabine (FTC)/efavirenz (EFV). Methods: A prospective, open-label, randomized controlled study was conducted. Eligible patients were ART naïve HIV individuals who initiated TDF/FTC/EFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It is known that vitamin D supplementation improves TDF‐associated PTH elevations [19] and vitamin D plus calcium supplementation improves endocrinological and BMD changes associated with TDF use as treatment in HIV infection populations [26‐28]. To date, there are limited data demonstrating the effect of vitamin D and calcium supplementation in youth PrEP users.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that vitamin D supplementation improves TDF‐associated PTH elevations [19] and vitamin D plus calcium supplementation improves endocrinological and BMD changes associated with TDF use as treatment in HIV infection populations [26‐28]. To date, there are limited data demonstrating the effect of vitamin D and calcium supplementation in youth PrEP users.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found similar results in HIV-negative populations taking PrEP ( 21 ). However, other studies did not find significant differences in changes of the hip and lumbar bone density among people living with HIV/AIDS (PLWHA) in both the VD and calcium supplementation group and the placebo group ( 26 ). Another study reported that there was no difference in the lumbar spine BMD in HIV-negative participants who participated in PrEP studies (−2.11 vs. −2.14%, p = 0.40) ( 27 ).…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies show that it is recommended a daily intake of calcium (1000mg/day) that is usually cover with a balanced diet (with protein). I case of low calcium intake, calcium and vitamin D supplements should be consider as they are known for lower bone mineral density loss [24]. Regulary physical activity should be promoted and stopping toxic habits just as smoking, use of drugs and alcohol.…”
Section: Prevention and Different Treatmentsmentioning
confidence: 99%